New Insights into Morphometry Studies - Pares-Casanova, Pere M. (IntechOpen, 2017)
There have been brilliant studies in the field of morphometry in recent years. This book increases the literature on this domain by presenting some recent advances and emerging applications upon biological structures, ranging in a variety of purposes and objectives: from animal visual system to growth models, from amphibians to humans, all in a comprehensive and accessible way of information. All chapters are written by leading internationally recognized experts from academia, who explain their own topics in plain English and in a totally rigorous manner. Suitable for a wide range of expert readers, this book represents a high valuable work for scientists and advanced students working in biological and medical morphometric topics.